2002
DOI: 10.1088/0960-1317/12/3/306
|View full text |Cite
|
Sign up to set email alerts
|

Novel MEMS pressure and temperature sensors fabricated on optical fibers

Abstract: This thesis presents the design, fabrication, and testing of novel MEMS pressure and temperature sensors fabricated on optical fiber end faces. A simple micromachining process compatible with MEMS was developed in fabricating sensors directly on optical fibers. The pressure sensor configuration involves anodic bonding of a piece of an extremely thin silicon wafer onto the fiber end face over a cavity etched in the central portion of the fiber end face. Final device diameter is thus the same as that of the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…Operating temperatures up to 800 • C have been achieved with sapphire membranes [1]. An interferometer-based sensor has also been fabricated inside a fiber-optic cable [2]. Another sensing technology uses Bragg gratings, which are photoinscribed into fibers and used to trace wavelength shifts caused by pressure and temperature changes at temperatures exceeding 350 • C and potentially over 1500 • C [3].…”
Section: Discharge-based Pressure Sensors Formentioning
confidence: 99%
“…Operating temperatures up to 800 • C have been achieved with sapphire membranes [1]. An interferometer-based sensor has also been fabricated inside a fiber-optic cable [2]. Another sensing technology uses Bragg gratings, which are photoinscribed into fibers and used to trace wavelength shifts caused by pressure and temperature changes at temperatures exceeding 350 • C and potentially over 1500 • C [3].…”
Section: Discharge-based Pressure Sensors Formentioning
confidence: 99%
“…In order to realize more functionality and applications, it is necessary to directly integrate electronic, computational and other functionality into textile fibers. Therefore, there are strong academic and industry interests in developing high resolution micromachining technology on fiber substrates [1][2][3][4]. As a matter of facts, practical applications cannot be expected unless the aforementioned micromachining technology can be utilized for mass production because the fiber substrates are not compatible with batch processes.…”
Section: Introductionmentioning
confidence: 99%
“…Although good results had been achieved, both the processes are mainly shadow-mask-based so that their applications are limited. Abeysinghe et al [4] and Sasaki et al [5] successfully demonstrated single fiber-based sensor for optical communication application but both sensors are made on the optical fiber end by using traditional photolithography technology. Therefore, we have recently suggested a so-called three-dimensional photolithography method for realizing the continuous photolithography process on the fibers [1].…”
Section: Introductionmentioning
confidence: 99%